Closing the mismatch: Encouraging jobseekers to reskill for shortage occupations - Elisabeth Leduc; Ilan Tojerow (Tinbergen Institute, 2025)
We partner with a Public Employment Service to examine whether jobseekers can be encouraged to reskill for shortage occupations. In a large-scale field experiment involving 100,000 recently unemployed individuals, we provide information on shortage occupations and related training opportunities. The intervention increased participation in transversal training courses by 6%, but did not boost enrolment in occupational training for shortage jobs. Jobseekers also shifted their search towards high-demand occupations, yet employment remained unchanged. These findings suggest that while low-cost informational interventions can influence job search and training behaviour, different approaches are likely needed to drive substantial reskilling among jobseekers.
Keywords: J24; J68; 330; Unemployment; Job Search; RCT; Occupational Training; Labour Shortages